LEGAL ASPECTS OF AUTONOMOUS VEHICLES – AN OVERVIEW - Novriansyah, Beldi; Surya, Edi; Destriani, Mellanie; Hendri, Taufik; Untung, DB.; Nelly, Nelly; Suryadi, Suryadi; Fikri, KMS. Novyar Satriawan (International Journal of Multidisciplinary Research and Literature, 2025)
The primary objective of this page is to furnish current information regarding the legal regulation of autonomous vehicles (AVs) in Indonesia. The legal overview is primarily designed for technical professionals to provide them with a comprehensive understanding of autonomous vehicles (AVs). The authors assert that technical professionals must be cognizant of the legal regulations governing autonomous vehicles to engage in discussions regarding the viability of various legal provisions.   In addition to defining AVs according to levels of automation, the article addresses the following inquiries: What are the primary advantages of autonomous vehicles? What modifications are necessary in the general road traffic legislation to permit the operation of autonomous vehicles on public thoroughfares? What are the distinctions between the present status of autonomous vehicle rules in the United States and Europe? Ultimately, the study highlights the most critical legal difficulties that autonomous vehicles provide to legislators, insurance providers, consumers, and, importantly, automobile manufacturers